WUJUD PILIHAN BAHASA MASYARAKAT KOTA PEKALONGAN ETNIS JAWA–TIONGHOA DALAM RANAH PERDAGANGAN - Adyana, M.Pd., Sulis (Widya Warta, 2020)
Pekalongan society is a multiethnic and multilingual society, including Javanese and Chinese. Language selection in multilingual communities is necessary so that the communication runs smoothly in accordance with the purpose. Speakers and interlocutors in Pekalongan City have differences in culture and ethnics. In this case, the language choice used in a multilingual society is based on the utterance's context and purpose. The condition of Pekalongan City, which is multiethnic and multilingual, raises inter-ethnic language contact. Language contact makes the speakers and interlocutors need to determine the appropriate use of language choice. The process of language selection is done to determine which languages are appropriate to use in the speech events of trade domain. This study aimed to describe the form of language choice of Javanese and Chinese ethnic groups in Pekalongan City in the trade domain. The data in this study were the fragments of the utterances in the trade domain, which were collected by observing method and were applied recording technique as the basic technique. Then, it was continued with further techniques, namely observation technique, recording technique, and noting technique. Furthermore, the data analysis was conducted by ethnographic methods. The forms of language choice of Javanese and Chinese ethnics in Pekalongan City in the trade domain were intra-language variations, code-switching, and code-mixing.